1996
DOI: 10.1007/bf00334652
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in the resistance to flooding and drought in populations of Paspalum dilatatum from different topographic positions

Abstract: Many studies have analysed plant responses to flooding or drought separately, without addressing the relations between plant resistance to each of these factors. In this paper, we compare the responses to drought and flooding under glasshouse conditions of three populations of Paspalum dilatatum, a perennial C grass dominant at different positions along a topographic gradient in the flooding pampa of Argentina. Our results showed that flooding effects on yield were negative on an upland, null on an intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 29 publications
5
62
0
3
Order By: Relevance
“…In the present study, drought did not have any impact on absolute change in root biomass in both species. Similar results have been reported by Loreti and Oesterheld (1996) with Paspalum dilatatum. Results from this study corroborate earlier findings (Huang and Gao, 2000) in that, high biomass fraction was partitioned in to roots during drought.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, drought did not have any impact on absolute change in root biomass in both species. Similar results have been reported by Loreti and Oesterheld (1996) with Paspalum dilatatum. Results from this study corroborate earlier findings (Huang and Gao, 2000) in that, high biomass fraction was partitioned in to roots during drought.…”
Section: Discussionsupporting
confidence: 91%
“…Even grass species with a known tolerance to flooding show a shift in carbon allocation from below-to above-ground components under flooding (Naidoo & Naidoo, 1992;Naidoo & Mundree, 1993;Baruch, 1994a;Loreti & Oesterheld, 1996;Dias-Filho & Carvalho, 2000). The reason for that is the deleterious effect flooding has on root formation and growth and the induction of root decay it causes (Kozlowski, 1997).…”
Section: Treatment Lmr Cmr Rmr ------------------------(Kg Kg -1 )---mentioning
confidence: 99%
“…These results support previous work on P absorption in waterlogged P. dilatatum plants (Rubio et al, 1997), where it was found that waterlogging increases P uptake per unit root as a consequence of (i) an increase in specific root length ; (ii) an increase in the intrinsic uptake capacity of each unit of root biomass (higher V max ; lower K m ) ; and (iii) an increase in soil P availability. A primary effect of soil waterlogging on these and many other tolerant plants is to produce a root system with more porosity, and this factor is presumably important to the increase in specific root length (Loreti & Oesterheld, 1996). It has been suggested that decreased soil penetration resistance under waterlogging conditions also contributes to the increase in specific root length (Rubio et al, 1997).…”
Section: mentioning
confidence: 99%